Syringa oblata genome provides new insights into molecular mechanism of flower color differences among individuals and biosynthesis of its flower volatiles - Chen, Lifei; Xia, Bin; Li, Ziwei; Liu, Xiaowei; Bai, Yun; Yang, Yujia; Gao, Wenjie; Meng, Qingran; Xu, Ning; Sun, Ying; Li, Qiang; Yue, Liran; et al. (Frontiers in Plant Science, 2022)
Syringa oblata is a high ornamental value tree owing to its elegant colors, unique aromas and wide adaptability, however, studies on the molecular mechanism underlying the formation of its ornamental traits are still lacking. Here, we presented a chromosome-scale genome assembly of S. oblata and the final genome size was 1.11 Gb, anchored on 23 chromosomes, with a contig N50 of 4.75 Mbp and was a better reference for S. oblata transcriptome assembly. Further by integrating transcriptomic and metabolic data, it was concluded that F3H, F3'H, 4CL and PAL, especially the F3'H, were important candidates involved in the formation of floral color differences among S. oblata individuals. Genome-wide identification and analysis revealed that the TPS-b subfamily was the most abundant subfamily of TPS family in S. oblata, which together with the CYP76 family genes determined the formation of the major floral volatiles of S. oblata. Overall, our results provide an important reference for mechanistic studies on the main ornamental traits and molecular breeding in S. oblata.